BREAST METASTASIS OF GASTRIC SIGNET RING CELL CARCINOMA MIMICKING BREAST LYMPHANGITIC CARCINOMATOSIS - Andrade, Raffaela Levy de; Buzzellin, Mauricio Nunes; Cançado, Adriana Viana; Pires, Douglas de Miranda (Mastology, 2019)
Introduction: The incidence of breast metastasis from gastric adenocarcinoma is extremely low. Since 1908, 44 cases have been reported in the literature, of which 30 are signet ring cell type. Case report: A 49-year-old patient being investigated for digestive bleeding was found to have left axillary lymphadenopathy, associated with breast asymmetry, associated with breast asymmetry, edema and thickening of the skin. Breast ultrasonography showed a heterogeneous lesion in the left breast. Core biopsy histology was compatible with Lauren diffuse gastric adenocarcinoma with signet ring cells. There was positive immunohistochemical staining for CK7, CK20 and CDX2 and negative for RE, RP and ERB2. Our findings were compatible with gastric adenocarcinoma (lymphatic embolism), favoring the possibility of a secondary neoplasm. At the time of diagnosis, the patient already had radiological signs of multiple metastases. Discussion: Breast metastases of gastric carcinoma differ from primary breast cancer in histopathological features. The clinical manifestations of gastric cancer metastasis vary, but it is known that there is a greater tendency for inflammatory disorders compared to primary tumors. In the metastatic process, breast involvement may be the first event or occur in a context of multiple metastases. Most patients have a one-year survival after diagnosis. There is no gain in survival with breast surgery, but it can alleviate the symptoms in some cases. Conclusion: Gastric cancer with breast metastasis is a rare condition associated with poor prognosis. The diagnosis is based on clinical history, histological findings and immunohistochemical markers, differing from primary tumors of the breast, to provide patients with adequate treatment.